Association between exercise self-efficacy and physical activity in elderly individuals: a systematic review and meta-analysis - Xie, Lei; Ma, Wenxue; Du, Kangli; Huang, Ying; Li, Aihua; Wang, Hongwei; Cui, Hongcheng; Qiu, Wentao; Gao, Rong; Qu, Guofeng; Wang, Xishuai; Liu, Cong (Frontiers in Psychology, 2025)
ObjectiveIn an aging population, the problem of insufficient physical activity among the elderly is increasingly recognized. Exercise self-efficacy, a critical determinant of physical activity in this demographic, has garnered increasing attention recently. This review focuses on healthy older adults, systematically reviewing the research progress on the relationship between exercise self-efficacy and physical activity in later life. It analyzes the correlation between the two factors and their influencing factors, and explores the mechanism of exercise self-efficacy in promoting physical activity among the elderly.MethodsIn accordance with the standards set by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, an extensive literature search was conducted across five electronic databases: Web of Science, PubMed, ProQuest, Scopus, and EBSCOhost. The search period spanned from January 1, 2000, to October 20, 2024. A rigorous quality assessment was performed on the selected studies, with methodological and outcome data extracted via a standardized data extraction form. The meta-analysis of the included studies was conducted via Stata 18 software, along with tests for between-study heterogeneity and an evaluation of publication bias.ResultsThe literature screening process yielded 19 studies that provided data on the correlation between physical activity and exercise self-efficacy. These studies employed Pearson correlation analysis (15 studies), multiple regression analysis (6 studies), and structural equation modeling (SEM) (4 studies). A random-effects model was used to pool the effect sizes, revealing an average correlation coefficient of r = 0.412 (p < 0.001). The average standardized coefficient for the effect of exercise self-efficacy on physical activity was β = 0.386 (p < 0.001), and the average path coefficient for the effect of physical activity on exercise self-efficacy was γ = 0.481 (p < 0.001).ConclusionA significant positive correlation was found between exercise self-efficacy and physical activity among elderly individuals, with a moderate degree of influence of exercise self-efficacy on physical activity participation. Conversely, physical activity also positively impacts exercise self-efficacy in elderly individuals. These findings provide a theoretical basis for encouraging elderly individuals to engage in physical activities and enhance their quality of life. Future research should further investigate the roles of various influencing factors and develop targeted intervention strategies to promote more active participation in physical activities among elderly individuals.